2022
DOI: 10.1001/jama.2022.17045
|View full text |Cite
|
Sign up to set email alerts
|

US Trends in Drug Overdose Mortality Among Pregnant and Postpartum Persons, 2017-2020

Abstract: This study evaluates changes in overall and drug-specific overdose mortality among pregnant and postpartum persons before and during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 5 publications
0
33
0
Order By: Relevance
“…Research has reported increases in pregnancy-associated drug overdose mortality . To inform substance use policy and practice, it is important to understand trends in unintentional or undetermined-intent pregnancy-associated overdose mortality caused by common psychotropic drugs of misuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has reported increases in pregnancy-associated drug overdose mortality . To inform substance use policy and practice, it is important to understand trends in unintentional or undetermined-intent pregnancy-associated overdose mortality caused by common psychotropic drugs of misuse.…”
Section: Introductionmentioning
confidence: 99%
“…esearch has reported increases in pregnancy-associated drug overdose mortality. [1][2][3][4] To inform substance use policy and practice, it is important to understand trends in unintentional or undetermined-intent pregnancy-associated overdose mortality caused by common psychotropic drugs of misuse. Considering that overall drug overdose mortality has increased significantly from 2018 through the COVID-19 pandemic, 5 an examination of trends in pregnancy-associated mortality from drug overdoses by pregnancy timing, age, race and ethnicity, educational attainment, and marital status during this time frame is warranted.…”
mentioning
confidence: 99%
“…O pioid use disorder (OUD) is a national epidemic, and overdose deaths increased approxi-mately 81% among pregnant and postpartum people between 2017 and 2020. [1][2][3] Postpartum is a particularly high-risk period, with increased risk of relapse, overdose, and death compared with during pregnancy. 3,4 Patients in the late postpartum period, defined as more than 6 weeks to 1 year postpartum, have higher overdose mortality rates compared with pregnant and early postpartum people.…”
mentioning
confidence: 99%
“…A major strength of this study is that Medicaid data are linked with the National Death Index, improving the identification of individuals by pregnancy status and timing of death at the national level. 2,4,5 Because most overdose deaths occur outside of the hospital setting, relying only on hospital codes likely underascertains the true burden of overdose death in this population. Although this study's design does improve ascertainment, it does not include miscarriage and abortions or individuals not insured by Medicaid before delivery.…”
mentioning
confidence: 99%
“…In this month's issue of Obstetrics & Gynecology , Suarez et al (see page 657) 1 add to the growing body of evidence showing that opioid overdose is a leading cause of death among postpartum individuals in the United States. 2–4 The authors analyzed a retrospective cohort of individuals insured by Medicaid at least 3 months before a live birth or stillbirth from 2006 to 2013. The authors found that, compared with the general population, individuals with opioid use disorder (OUD) were 24 times more likely to die in the year postpartum from opioid overdose (118 vs 5.4/100,000 deliveries) and six times more likely to die from any cause (316 vs 51.1/100,000 deliveries).…”
mentioning
confidence: 99%